Digital Divide As A Modern Determinant Of Regional Income Inequality (A Case Study Of West Sumatra Province 2011-2024): DIGITAL DIVIDE SEBAGAI DETERMINAN MODERN DALAM KETIMPANGAN PENDAPATAN DAERAH (STUDI KASUS PROVINSI SUMATERA BARAT PERIODE 2011-2024) - Anisa Yulianti; Nelvia Iryani (Green Engineering Society, 2026)
Abstract. This study aims to analyze the implementation of the Agam Maju Generasi Pintar Scholarship Program in 2025 in Agam Regency using a quantitative descriptive approach. The study focuses on the distribution of scholarship recipients, the amount of assistance, and the program’s contribution to improving access to higher education. The data used are secondary data obtained from the Regent’s Decree of Agam Regency in 2025 and publications from the Central Bureau of Statistics. The analysis method employs descriptive statistics in the form of percentages and tabulation. The results show that the total number of recipients is 270 students, dominated by continuing recipients (95.9%), while new recipients account for only 4.1%. The decrease in recipients is influenced by the implementation of DTSEN-based verification. The amount of assistance varies based on the location of the university, indicating a need-based policy approach. Overall, the program contributes to improving access to higher education, although it still functions as supplementary financial support. Abstrak. Penelitian ini menganalisis pengaruh kesenjangan digital (digital divide) terhadap ketimpangan pendapatan dengan Indeks Pembangunan Manusia (IPM) sebagai variabel kontrol pada kabupaten/kota di Provinsi Sumatera Barat periode 2011–2024. Data sekunder dari Badan Pusat Statistik (BPS) dianalisis menggunakan regresi data panel. Hasil penelitian menunjukkan bahwa digital divide berpengaruh negatif dan signifikan terhadap ketimpangan pendapatan, sehingga peningkatan akses internet cenderung menurunkan ketimpangan. IPM tidak berpengaruh signifikan secara langsung, namun mendukung pemanfaatan teknologi digital oleh masyarakat. Secara simultan, digital divide dan IPM berpengaruh terhadap ketimpangan pendapatan. Temuan ini menegaskan pentingnya pemerataan akses teknologi dan peningkatan kualitas sumber daya manusia untuk mengurangi ketimpangan ekonomi daerah.